INTERNALISASI NILAI SPIRITUAL MELALUI INTERAKSI GURU PAI DENGAN SANTRI DI DAYAH MODERN ACEH BESAR - Subhan Muhammad Isa (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The pattern of interaction between teachers and students may differ from one educational institution to another. The interaction between teachers and students in schools is generally limited to the pattern of transferring knowledge from one party to another, and it does not create an atmosphere of intimacy and kinship. The interaction between teachers and students in modern dayah tends to be equal, full of intimacy and warmth. This bond can make students more effective in modeling the behavior and values of the teacher by the students. Through multi-directional interaction patterns in the classroom and interaction patterns based on affection, familiarity, gentle and firm communication patterns, Islamic education teachers in the modern dayah of Aceh Besar have had a significant impact in internalizing spiritual values in students.